Wealth and asset price effects on economic activity - Filippo Altissimo; Evaggelia Georgiou; Teresa Sastre; Maria Teresa Valderrama; Gabriel Sterne; Marc Stocker; Mark Weth; Karl Whelan; Alpo Willman (European Central Bank (ECB), 2005)
Do asset prices affect real activity? This question has taken on a new importance in recent years, as asset values first surged at the end of 1990s and, thereafter, dramatically retreated. This report reviews the available theoretical and empirical evidence regarding asset price and wealth effects in Europe and some other major economies. The main focus of this report is on consumption effects via the wealth channel, reflecting the bulk of literature on the effects of asset prices. However, asset price effects on investment via the Tobin's-Q channel, balance sheet and confidence channels are also reviewed. The available evidence supports the view that the wealth channel is the most important of various channels. There is little empirical evidence indicating that the Tobin's-Q, balance-sheet and confidence channels play any major independent role in the transmission of asset price effects to economic activity.
Keywords: D1; D3; D9; G11; 330; household wealth; wealth channel; asset price; marginal propensity to consume; cost of capital.; Vermögenseffekt; Wirtschaftswachstum; EU-Staaten